2014
DOI: 10.1002/ejlt.201400222
|View full text |Cite
|
Sign up to set email alerts
|

Identification and quantification of canolol and related sinapate precursors in Indian mustard oils and Canadian mustard products

Abstract: Canadian condiment yellow mustard seeds (also called white), oriental and brown mustard seeds and flour extracts and commercially produced Indian mustard oils were examined for bioactive phenolics primarily to identify the antioxidant properties. Phenolic compounds, namely sinapic acid, sinapoyl glucose and canolol, were quantified using high-performance liquid chromatographic (HPLC) coupled with a diode array detector (DAD). Canolol was detected and confirmed in trace amounts for the first time in commercial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 51 publications
(88 reference statements)
2
15
0
Order By: Relevance
“…Pojić et al () found that the content of phenolic compounds in the meal was higher than for cold‐pressed hempseed oil. These results corroborate the fact that phenolic compounds are mostly present in the seed portion, even if smaller amounts may be transferred to the oil during pressing processes (Chen et al, ; Pojić et al, ; Thiyam‐Holländer et al, ).…”
Section: Resultssupporting
confidence: 82%
“…Pojić et al () found that the content of phenolic compounds in the meal was higher than for cold‐pressed hempseed oil. These results corroborate the fact that phenolic compounds are mostly present in the seed portion, even if smaller amounts may be transferred to the oil during pressing processes (Chen et al, ; Pojić et al, ; Thiyam‐Holländer et al, ).…”
Section: Resultssupporting
confidence: 82%
“…Converting these values in mass ratio leads to a total phenolic content of 9.00 mg ESE/g DDM with sinapine representing 5.65 mg/g DDM (63%). It is noteworthy to mention that this ratio is similar to that reported by Thiyam-Holländer et al (2014) on flour of mustard but lower than those reported for cotyledon, hull, and seed by Mayengbam et al (2014)…”
Section: Folin-ciocalteu Methodologysupporting
confidence: 62%
“…Various extraction methods were reported to extract different parts of the mustard such as seed (Amarowicz et al, 1996;Kozłowska et al, 2016;Thangi et al, 2016), flour (Thiyam-Holländer et al, 2014), leaf (Santos et al, 2014;Park et al, 2017), hull and cotyledon (Mayengbam et al, 2014), or meal (Engels et al, 2012;Dubie et al, 2013). The most popular technique uses a mixture of methanol or ethanol in water (Song et al, 2010;Huang et al, 2012;Li et al, 2012;Thiyam-Holländer et al, 2014;Park et al, 2017), and often coupled to ultrasound (Thiyam et al, 2004;Terpinc et al, 2012;Dubie et al, 2013;Mayengbam et al, 2014;Szydlowska-Czerniak et al, 2015). Some papers also described extraction methods involving only osmotic water (McCue et al, 2005;Thangi et al, 2016), pressurized solvent (Santos et al, 2014), a mixture of methanol and chloroform (Ishtiaque et al, 2013;Kozłowska et al, 2016), or a mixture of acetone, or methanol and 0.1% formic acid (Engels et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The influence of roasting treatments on TPC has been previously described (Spielmeyer et al, 2009;Thiyam-Hollaender et al, 2014). Subjecting the meal to simple roasting treatments at 105 • C for SR-H0 and 160 • C for SRSH-H0 decreased the TPC contents by 11% and 27%, respectively (Table 2, Fig.…”
Section: Thermal Treatments Effectmentioning
confidence: 78%
“…These results could be explained by a thermal degradation of phenolics. In contrast, smaller differences in TPC contents were measured between the original meal and microwave treated samples (4% of decrease for both MWR-H0 and MWRSH-H0) suggesting that microwaves energy would result either in a lower thermal degradation of phenolic compounds or in a more efficient release of phenolics initially linked to proteins or carbohydrates after partial breakage of the plant cell walls (Khattab et al, 2014;Thiyam-Hollaender et al, 2014;Yang et al, 2014).…”
Section: Thermal Treatments Effectmentioning
confidence: 89%